Hemorrhagic tonsillitis in an infant: A case report. (September 2020) - Wilson, J. David; Zeisler, Bella; Grover, Nancy
Abstract: This case report describes a case of severe hemorrhagic tonsillitis in a nine month-old child who suffered significant amount of blood loss and was emergently taken to operating room for control of hemorrhage. The child was brought to emergency room by mom after noticing blood around child's mouth and nose and a subsequent episode of hematemesis having awoken from sleep. Initial impression was bleeding secondary to epistaxis however a thorough bedside otolaryngology exam including flexible rhinolaryngoscopy ruled this out. Rapid pooling of blood in oropharynx, continued hemorrhage with significant blood loss and recent history of hematemesis prompted emergent intervention in operating room for endoscopy for control of hemorrhage including esophagogastroduodenoscopy (EGD). Bleeding was identified from a blood vessel at left lower tonsil pole. Although there is a description in literature of such cases, these are uncommon in the pediatric population and none has been described in a patient this young requiring emergent operative intervention. This case report discusses the diagnostic and decision making dilemma in an infant in setting of ongoing active hemorrhage and the role of multidisciplinary team management.